A Study on the Impact of Sleep Deprivation on University Girl Students (International Journal of Preventive Medicine and Health (IJPMH), 2026)
Sleep is necessary for overall well-being, emotional regulation, and cognitive performance. Many students suffer from chronic sleep loss caused by social commitments, technological distractions, and academic pressure. Their mental health suffers significantly as a result of the lack of sleep, with symptoms including increased stress, anxiety, sadness, and cognitive deterioration. Parents, educators, and children must understand the relationship between sleep and mental health. Encouraging kids to sleep well can make their lives better in many ways, including their health, schoolwork, and mental health. A variety of biological and social factors can cause sleep loss, a common condition. The study was conducted at Babasaheb Bhimrao Ambedkar University on 100 undergraduate and postgraduate female students. The study shows that poor sleep quality harms female students.